IMPROVED REFORMS IN UZBEKISTAN REGARDING MOTHER AND CHILD HEALTH CARE - Abdurakhmon Abdumuminovich Abdukhalimov (Journals Park Publishing, 2023)
The article analyzes the reforms carried out in the country during the years of independence in the field of maternal and child health care, medical services, birth rates and death rates.
Keywords: Republic, mother and child, medical service, screening centers, health promotion, reproductive health.